TINDAK PIDANA DALAM AKSI DEMOSTRASI YANG ANARKIS DITINJAU BERDASARKAN UU NO. 9 TAHUN 1998 TENTANG KEMERDEKAAN MENGELUARKAN PENDAPAT DI DEPAN UMUM - Ica Karina, S.H.,M.H (JURNAL JUSTIQA, 2021)
Demonstrations are a part of democratic life in a country because demonstrations are away to express opinions in public. The demonstrations that have occurred recently havebasically become increasingly widespread since the fall of the New Order regime, in thisregard the Indonesian people have begun to see, hear and even get involved eitherdirectly or indirectly in demonstration activities. This irresponsible demonstrationcertainly violates the provisions contained in the Criminal Code and Law Number 9 of1998 concerning Freedom to Express Opinions in Public. The purpose of this study wasto determine the factors that cause anarchist demonstrations and to find out what steps can be taken to prevent demonstrations from turning into acts of anarchism. The datacollection technique used in this research is through literature study to obtainconceptions, theories or doctrines, opinions or conceptual thoughts from previousresearchers related to the object of this research which can be in the form of laws andregulations or other sources. This research is analytical descriptive, the type of researchthat will be conducted in this research is juridical research. Without legal certainty therewill be no order. On the other hand, at a certain level, order can undermine justice. Inaddition to realizing certainty, order requires equality, while justice must allow fordiversity or differences in treatment. The description above just wants to show that legalissues are not as simple as they are often touted.